Economic Empowerment of Women Pourers and Palamitras in Dairying in Chittoor District, Andhra Pradesh - P. Jyoshna; P. Tarangini and B. Bhagavan Reddy (Commerce Spectrum, 2014)
To take advantage of government policy and programme women enter into dairying on a large scale in Chittoor district. The freedom of respondents in spending their income had greatly increased among pourers and palamitras. A good percentage of respondents have declined in the lower option, moved up in the middle option and formed afresh in the higher option in the post dairying period. The number of respondents with no control over income and their classifications on the basis of age, education, caste affiliation, nature of family and level of monthly income has decreased in the post-period. A contrary situation prevails in the case of respondents who have control over income to some extent. Further, none of the respondents have enjoyed control over income to a great extent in the pre-period but they are found afresh across all the variables in the post-period.More than 60 per cent of pourers and 44 per cent of palamitras have saved less than Rs. 3000 per month in the post dairying period. The share of respondents who believe that there was no control over family resources became negligible in the post- period. Evidently, there is an increase in the number of respondents with control over family resources in the post- dairying period. The respondents with ‘control over family resources to a great extent’ have formed in the after- period only. The respondents who had enjoyed ‘no control over resources’ have decreased correspondingly increasing the share of respondents who had exercised control over resources to some extent in the post-period. No doubt, dairying has resulted in the economic empowerment of women.